2015
DOI: 10.1155/2015/806725
|View full text |Cite
|
Sign up to set email alerts
|

Three Cases of Previous Smokers with Rheumatoid Arthritis Who Did Not Respond to Tumor Necrosis Factor Inhibitors Were Treated Successfully with an Anti-Interleukin-6 Receptor Antibody

Abstract: We report three cases of previous smokers who did not respond to TNF inhibitors but who responded successfully to an anti-interleukin-6 receptor antibody (tocilizumab (TCZ)). Case 1 is a 63-year-old woman whose smoking index was 200 and had been complaining of polyarthralgia since 1996. She started treatment with etanercept due to high disease activity, but her DAS28-CRP was 4.2. She was therefore switched to TCZ, which dramatically improved her symptoms; her DAS28-CRP had decreased to 2.1. Case 2 is a 64-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Clinical studies have shown that smoking can interact with certain medications affecting their absorption, distribution, metabolism, and/or elimination 54 . For example, it has been suggested that patients with RA who smoke require higher doses of disease modifying antirheumatic drugs (DMARD) as the potency of antirheumatic agents may be reduced 55–57 . However, it remains unclear if these findings are a consequence of indirect or direct chemical interactions with joint tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies have shown that smoking can interact with certain medications affecting their absorption, distribution, metabolism, and/or elimination 54 . For example, it has been suggested that patients with RA who smoke require higher doses of disease modifying antirheumatic drugs (DMARD) as the potency of antirheumatic agents may be reduced 55–57 . However, it remains unclear if these findings are a consequence of indirect or direct chemical interactions with joint tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…54 For example, it has been suggested that patients with RA who smoke require higher doses of disease modifying antirheumatic drugs (DMARD) as the potency of antirheumatic agents may be reduced. [55][56][57] However, it remains unclear if these findings are a consequence of indirect or direct chemical interactions with joint tissues and cells. Additionally, CSE has been shown to impair the ability of OA-affected chondrocytes in vitro to respond to hyaluronic acid treatment.…”
Section: Importance Of Studying Cigarette Smoke's Impact On Oa and St...mentioning
confidence: 99%